Potensi Mengembang Hidrogel Komposit Chitosan dengan Tulang Sapi Demineralisasi Beku Kering untuk Regenerasi Tulang - Wardani, Sinta Candra; Pratiwi, Ariyati Retno; Istikharoh, Feni; Pramaiswari, Made Adelia; Margareta, Isti Tri Aulia (E-Prodenta Journal of Dentistry, 2026)
Backgrounds: Demineralized freeze-dried bovine bone synthesized in nanoparticle size is expected to improve the osteoinductive of chitosan hydrogel as bone regeneration material. Therefore, an evaluation was carried out on whether this material can affect swelling as one of the physical properties of the hydrogel. Objective: To determine the swelling potential test of the hydrogel composite with varying concentrations of Demineralized Freeze-Dried Bovine Bone Nanoparticle (DFDBB-Np). Methods: The chitosan hydrogels at DFDBB-Np concentrations of 0%, 0.5%, 1%, 1.5%, 2%, and 2.5% are incubated in sterile water at 37°C for varying durations (3, 6, 12, 24 hours) until swelling occurs. The equilibrium Swelling Ratio (SR) is calculated as the ratio of the swelling to the initial weight. Results: After 24 hours of incubation, a significant difference was observed between concentrations of 0% and 0.5%, 1%, 1.5%, 2%, and 2.5% (sig = 0.015, 0.004, 0.000, 0.001, 0.000). However, other concentrations and duration did not show any significant difference. Conclusion: DFDBB-Np retains its potential as a composite material with chitosan hydrogel for bone regeneration.